2018
DOI: 10.1007/s00380-018-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of homocysteine and dimethylarginines on cardiovascular mortality in claudicant patients with lower extremity arterial disease

Abstract: The association among serum homocysteine (HCY), symmetric dimethylarginine (SDMA), and asymmetric dimethylarginine (ADMA) is of interest in endothelial dysfunction, although the underlying pathology is not fully elucidated. We investigated the relationship of HCY with SDMA and ADMA regarding their long-time outcome and the age dependency of HCY, SDMA, and ADMA values in claudicant patients with lower extremity arterial disease. 120 patients were included in a prospective observational study (observation time 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Increased NO bioavailability may improve endothelial function, blood flow and vasodilatory capacity 22 , contributing to increase walking capacity, mobility and independent living. As endothelial dysfunction 47 , oxidative stress 48 and inflammation 21 are associated with morbimortality and disease progression in IC, their improvement may reduce cardiovascular risk and ameliorate prognosis. Thus, the present study provided novel evidence (systemic and local) about the benefic effects of a submaximal WT on key factors associated with PAD progression and cardiovascular risk (a complete hypothetic model can be seen in graphical abstract).…”
Section: Resultsmentioning
confidence: 99%
“…Increased NO bioavailability may improve endothelial function, blood flow and vasodilatory capacity 22 , contributing to increase walking capacity, mobility and independent living. As endothelial dysfunction 47 , oxidative stress 48 and inflammation 21 are associated with morbimortality and disease progression in IC, their improvement may reduce cardiovascular risk and ameliorate prognosis. Thus, the present study provided novel evidence (systemic and local) about the benefic effects of a submaximal WT on key factors associated with PAD progression and cardiovascular risk (a complete hypothetic model can be seen in graphical abstract).…”
Section: Resultsmentioning
confidence: 99%
“…Homocysteine (Hcy), a metabolic by-product of methionine, is an essential amino acid derived from dietary protein. 1 High levels of Hcy or hyperhomocysteinemia (HHcy) increases the risk of heart and vascular diseases, 2 as well as other pathological conditions, such as encephalopathy, kidney disease, and liver disease. 3 , 4 Previous studies have shown that Hcy results in increased collagen synthesis and deposition in animal hearts, kidneys, and carotid arteries.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation leads to loss of more than 60% of MTHFR enzymatic activity [20], and 8% of general population is homozygous for this variant. In these patients, folate level interferes directly with plasma homocysteine content, and this is only increased when folate concentration is below 15.4 nmol/L [27][28][29][30]. This mutation can be present together with the CBS mutation.…”
Section: Introductionmentioning
confidence: 99%
“…It is more common in men (21% above women) and increases in women during menopause [28]. There is also an increase with age and, since elderly patients show bigger vitamin deficiency, hyperhomocysteinemia is, in this group of individuals, an important risk factor for coronary disease [29,30]. individuals, ranging from 5 to 15 µmol/L [2,12,13].…”
Section: Introductionmentioning
confidence: 99%